A tin porphyrin axially-coordinated two-dimensional covalent organic polymer for efficient hydrogen evolution. Issue 53 (13th June 2022) - Wang, Qi; Wang, Aijian; Dou, Yuqin; Shen, Xiaoliang; Sudi, M. Shire; Zhao, Long; Zhu, Weihua; Li, Longhua
Abstract : The prepared tin porphyrin axially-coordinated 2D covalent organic polymer exhibits excellent HER activity due to its unique structural properties, ranking among the best records reported recently. Abstract : Herein, we demonstrate a facile strategy for constructing an efficient and stable hydrogen evolution reaction (HER) catalyst, i.e. a tin porphyrin axially-coordinated 2D covalent organic polymer (SnTPPCOP). SnTPPCOP exhibits promising HER activity with a low overpotential of 147 mV at 10 mA cm −2 due to its unique structural properties, ranking among the best records reported recently.